Songs and morphology in grasshoppers of the Stenobothrus eurasius group (Orthoptera: Acrdidae: Gomphocerinae) from Russia and adjacent countries: clarifying of taxonomic status - Tarasova, Tatiana A.; Sevastianov, Nikita S.; Vedenina, Varvara Yu. (Zootaxa, 2021)
On the basis of the song and morphological analyses, we revised the status of the subspecies Stenobothrus eurasius eurasius Zubowsky, 1898, and S. eurasius hyalosuperficies Vorontsovskii, 1927. The status of the subspecies S. eurasius hyalosuperficies Vor. has been changed to the species level. The most striking difference between S. eurasius and S. hyalosuperficies lies in the song parameters. The calling songs differ not only in temporal parameters but are also produced by different mechanisms. S. eurasius generates calling songs by common leg stridulation, whereas S. hyalosuperficies produces sound by wing clapping. The courtship songs of both species are complex (contain several elements) and very different in temporal structure. The morphological differences between the two species are not as striking as the differences in bioacoustics: we found the only differences in the hind wing venation. At the same time, we suggest these differences to be important since they might be due to different mechanisms of sound production. We revised the ranges of the two species on the territory of Ukraine, Russia and Kazakhstan. We also reviewed the type localities of S. eurasius Zub. and designated lectotype and paralectotype of this species.